Production and optimization of l-asparaginase by e.coli atcc10536 from food waste - Batool, Tahira; Chia, Vi Vien; Makky, Essam A.; Nina Suhaity, Azmi; Mashitah, Mohd Yusoff (JOCPR, 2015)
The current study aimed at utilization of food waste as squid pen (SP) and cooked chicken bone (CCB) for Lasparaginase (LA) production and optimization using E.coli culture. During our investigations, high levels of Lasparaginase were obtained from E.coli using squid pen as a sole carbon source as compared to CCB. Optimization of parameters resulted in 2.5folds increase in the L-asparaginase activity. Optimum L-asparaginase production 4.316IU/mL was observed when production media was supplemented with 1%, (w/v) ammonium sulphate, 2%, (w/v) substrate at pH 9, and 37°C after incubation for 5 days.This study underlines the use of food waste as an alternate substrate for the production of L-asparaginase and to improve the cost effectiveness of this enzyme.